Pribumisasi Islam: Konsep Islam yang Ramah terhadap Budaya Lokal dalam Pandangan Abdurrahman Wahid - Puji Miftahul Arfi (Polyscopia, 2026)
The concept of the indigenization of Islam was articulated by Abdurrahman Wahid, widely known as Gus Dur, in the 1980s as a response to tensions between religious universalism and Indonesia’s plural cultural landscape. This study examines how Wahid conceptualized a culturally responsive Islam and addresses the question of whether indigenization constitutes syncretism or a contextualization of Islamic teachings within local traditions. Employing a qualitative content analysis method, the research analyzes primary and secondary written sources, including books and scholarly articles relevant to Wahid’s thought. The findings indicate that indigenization does not imply theological compromise but rather situates Islam within a cultural framework that allows its normative teachings—particularly in the domains of fiqh, customary practices, textual interpretation, and political-ideological articulation—to be socially grounded and dialogical. Wahid argues that Islam becomes socially transformative not through coercion, but through cultural resonance and ethical engagement. The study concludes that the indigenization of Islam represents a strategic intellectual effort to harmonize religious orthodoxy with Indonesia’s socio-cultural plurality, thereby strengthening Islam’s legitimacy within a democratic and multicultural society.